Perbandingan Kinerja Block Storage Ceph dan ZFS di Lingkungan Virtual - Faza Abdani Auni Robbi; Agung Budi Prasetijo; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
The growth of data requires better performance in the storage system. This study aims to analyze the comparison of block storage performance of Ceph and ZFS running in virtual environments. Tests were conducted to measure their performances, including IOPS, CPU usage, throughput, OLTP Database, replication time, and data integrity. Testing was done using 2 node servers with a standard configuration of the storage system. Server virtualization uses Proxmox on each node. ZFS has a higher performance of reading and writing operation than Ceph in IOPS, CPU usage, throughput, OLTP and data replication duration, except the CPU usage in writing operation. The test results are expected to be a reference in the selection of storage systems for data center applications.